'Nothing too major': how poor revision of writing may be an adaptive response to school tasks. (4th July 2019) - Oliver, Lucy
Abstract: This multicase study explores students' understandings about revision in the light of successive findings that they typically revise their texts little and at superficial levels. Students' limited revising has been variously explained, both in terms of cognitive-metacognitive factors and restrictive school models. Few studies, however, have examined students' thinking about revision. This investigation considers the impact students' concepts of purpose have on their revising and the extent to which perceived expectations and school routines inform the scope of their achievement. One-to-one observations of writing, post hoc interviews and analyses of students' texts were repeated over the course of an extended classroom writing task. Findings suggest that whilst students' definitions of revision were narrow and their text changes primarily superficial, they did not necessarily lack the understanding or skill to revise more effectively. Able writers explicitly chose an instrumental approach, attributing limited revision to tightly-prescribed and time-controlled tasks. They perceived a dichotomy between school purposes and more authentic possibilities. The study highlights the contextualised nature of students' decision-making and argues that poor revision may be an adaptive response to school requirements rather than an innate limitation.